2022
DOI: 10.1007/s10151-022-02693-y
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, randomized assessment of a novel, local antibiotic releasing platform for the prevention of superficial and deep surgical site infections

Abstract: Background Despite significant advances in infection control guidelines and practices, surgical site infections (SSIs) remain a substantial cause of morbidity, prolonged hospitalization, and mortality among patients having both elective and emergent surgeries. D-PLEX100 is a novel, antibiotic-eluting polymer–lipid matrix that supplies a high, local concentration of doxycycline for the prevention of superficial and deep SSIs. The aim of our study was to evaluate the safety and efficacy of D-PLEX i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 28 publications
(30 reference statements)
0
8
0
Order By: Relevance
“…By that, D-PLEX can provide controlled antibacterial activity directly at the surgical site, while keeping systemic antibiotic exposure very low. 9,13 The safety of D-PLEX in adult animals has been demonstrated previously in preclinical in vivo studies in a sternal surgical defect model in New Zealand white rabbits and in an abdominal surgical incision model in miniature swine. Full absorption of D-PLEX was observed after 9 and 6 months in both models, respectively.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…By that, D-PLEX can provide controlled antibacterial activity directly at the surgical site, while keeping systemic antibiotic exposure very low. 9,13 The safety of D-PLEX in adult animals has been demonstrated previously in preclinical in vivo studies in a sternal surgical defect model in New Zealand white rabbits and in an abdominal surgical incision model in miniature swine. Full absorption of D-PLEX was observed after 9 and 6 months in both models, respectively.…”
Section: Introductionmentioning
confidence: 87%
“…However, this method has limitations in its effectiveness since the local concentration of the given antibiotic at the surgical site may not reach the necessary levels, resulting in ineffective prophylaxis. [7][8][9] The medical conditions known to be associated with lower local concentrations include peripheral vascular disease, obesity, and diabetes. [9][10][11][12] To overcome this hurdle, various techniques for delivering antibiotics directly to the surgical site have been developed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that this novel matrix could be a promising addition to current SSI prevention bundles. 6…”
Section: Antibiotic Matrixmentioning
confidence: 99%
“…No significant differences in adverse events occurred between the two groups. The authors concluded that this novel matrix could be a promising addition to current SSI prevention bundles 6 …”
Section: Antibiotic Matrixmentioning
confidence: 99%